1995
DOI: 10.1002/bem.2250160306
|View full text |Cite
|
Sign up to set email alerts
|

3T3 cell motility and morphology before, during, and after exposure to extremely‐low‐frequency magnetic fields

Abstract: Automated image cytometry techniques were used to measure motility and morphology in 3T3 fibroblasts exposed to extremely-low-frequency (ELF) magnetic fields. Cell motility and morphology were measured as a function of time before, during, and after 3-4 hour exposures to vertically oriented, 100 microTRMS sinusoidal magnetic fields at various frequencies in the 10-63 Hz range. Sham exposures were also carried out. No static DC fields were applied, but the geomagnetic field was almost vertical and, therefore, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
(32 reference statements)
1
4
1
Order By: Relevance
“…Our results differ from those obtained by Spadinger et al [1995], who reported no evident effect of MFs on cellular changes in 3T3 fibroblasts.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results differ from those obtained by Spadinger et al [1995], who reported no evident effect of MFs on cellular changes in 3T3 fibroblasts.…”
Section: Discussioncontrasting
confidence: 99%
“…Efforts to replicate the studies of Spadinger et al [1995], using a longer exposure duration, resulted in remarkably similar ®ndings. That is, a 0.7 mT magnetic¯ux at 60 Hz, inducing a 0.5 mV/m rms electric ®eld, resulted on average in only slight morphologic changes to the cell population, none of which were signi®cant.…”
Section: Discussionsupporting
confidence: 60%
“…However, as the morphologic changes are consistently in one direction, it would be expected that analysis of larger cell numbers should show an effect of ®eld exposure at the levels used here even if orientation were not considered. As the tracking assay utilized by Spadinger et al [1995] restricted the analysis to a small number of cells (approximately 100), this orientation effect may help clarify why the morphologic changes they observed never reached statistical signi®cance. This observation may also provide some rationale for why many of the reported cellular responses to ELF ®eld exposures have the tendency to be remarkably small, as compared, for example, to pharmacologic intervention, even when the responses appear quite consistent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Available research at the cellular level deals with effects on osteogenesis and proteins, but there has been hardly any quantitative estimation of cell activities observable by a microscope, in particular, cell migration. Studies of cell migration conducted so far have dealt with one or a few cells in a Petri dish [15,16]. For example, Ref.…”
Section: Introductionmentioning
confidence: 99%